Innovation in an Arab Jawi-Based Chemistry Module Integrating Islamic Values on Reaction Rate Material at MA Zainatul Ulum - Hayatuz Zakiyah; Putri Novira; Safrijal Safrijal; Aris Munandar; Nur Jahan Ahmad; Teuku Badlisyah; Nida Ulya Mustika (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2026)
The innovation of an Arabic-Jawi chemistry module integrated with Islamic values on the topic of reaction rates was prompted by the scarcity of learning resources and the fact that available school modules are exclusively in the Indonesian script. Furthermore, this initiative serves as a positive step toward preserving Nusantara culture among students already familiar with Arab-Jawi. The internalization of Islamic values in this module’s development aligns with and supports the vision and mission of the Dayah (traditional Islamic boarding school). This study aims to determine the validity of the Arab-Jawi chemistry module integrated with Islamic values for the reaction rate topic at MA Zainatul Ulum, West Aceh Regency. The research design follows a research and development approach using the 4D model (define, design, develop, disseminate). The research subject is the Arab-Jawi chemistry module itself, featuring integrated Islamic values. Data collection instruments included interview guides and expert validation sheets. Data analysis was conducted by reducing interview data and analyzing the validation sheets. The validation results obtained from three experts reached 94.8%, falling into the 'highly valid' category. Based on these findings, it can be concluded that the Arab-Jawi chemistry module with internalized Islamic values on reaction rates is highly valid for instructional use